2019
DOI: 10.1111/cas.14245
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative monitoring of circulating tumor DNA in patients with advanced pancreatic cancer undergoing chemotherapy

Abstract: According to cancer genome sequences, more than 90% of cases of pancreatic ductal adenocarcinoma (PDAC) harbor active KRAS mutations. Digital PCR (dPCR) enables accurate detection and quantification of rare mutations. We assessed the dynamics of circulating tumor DNA (ct‐DNA) in patients with advanced PDAC undergoing chemotherapy using dPCR. KRAS G12/13 mutation was assayed by dPCR in 47 paired tissue‐ and ct‐DNA samples. The 21 patients were subjected to quantitative ct‐DNA monitoring at 4 to 8‐week intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…Therefore, our data cannot evaluate the impact of adjuvant chemotherapy on ctDNA. However, previous studies have confirmed the possible role of circulating DNA in judging the efficacy of chemotherapy (24,25). A well-designed clinical trial is needed to verify the role of ctDNA in evaluating the efficacy of neoadjuvant therapy for lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data cannot evaluate the impact of adjuvant chemotherapy on ctDNA. However, previous studies have confirmed the possible role of circulating DNA in judging the efficacy of chemotherapy (24,25). A well-designed clinical trial is needed to verify the role of ctDNA in evaluating the efficacy of neoadjuvant therapy for lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, progression free survival analysis revealed that ctDNA KRAS mutation patients undergoing first-line chemotherapy tended to have worse progression free survival than those without a KRAS mutation (median 308.5 vs. 168 days, p = 0.07). Interestingly, they showed that, in those cases with a KRAS mutation in ctDNA at the time of diagnosis, the KRAS mutation disappeared after the initial course of chemotherapy and reappeared concurrently with or earlier than progression of the disease, highlighting the predictive factor for disease progression of PDAC patients [ 59 ].…”
Section: Increasing Genetic Knowledge To Improve Clinical Practicementioning
confidence: 99%
“…In the near future, in addition to clinical followup, imaging assessment and measurement of conventional serum tumor markers such as CA 19.9, the monitoring of circulating tumor DNA, tumor cells or extra-cellular vesicles will help guide maintenance therapies in patients with PDAC. [41][42][43] This confirms the importance of carefully designing ancillary studies as well as those for treatment.…”
Section: Future Options For Maintenance Therapy Role Of Immunotherapymentioning
confidence: 64%